2020
DOI: 10.3390/ma13173685
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Fiber Lengths for Hot Mix Asphalt with Different Nominal Maximum Aggregate Size: A Pilot Experimental Investigation

Abstract: Fiber length is a key parameter for the mixture design of basalt fiber-reinforced hot mix asphalt (HMA), which significantly affects the mix performance. To evaluate the suitability of fiber lengths for HMA with different nominal maximum aggregate size (NMAS), basalt fiber with the lengths of 3, 6, 9, 12, and 15 mm were selected for dense graded gradations with different NMASs (namely, SUP-13, SUP-20, and SUP-25), so as to prepare the fiber-reinforced HMA mixtures. Then, the mix performance was evaluated by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Several measures were adopted to enhance the performance of the pavement [ 6 , 7 , 8 , 9 , 10 ]. The previous studies showed that adding fibers into the mixtures is an effective way [ 11 , 12 ]. Generally, the fibers added in the asphalt pavement could be divided into several categories such as the plant fibers (lignin fiber and bamboo fiber, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several measures were adopted to enhance the performance of the pavement [ 6 , 7 , 8 , 9 , 10 ]. The previous studies showed that adding fibers into the mixtures is an effective way [ 11 , 12 ]. Generally, the fibers added in the asphalt pavement could be divided into several categories such as the plant fibers (lignin fiber and bamboo fiber, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research carried out by our research group and actual engineering experience [ 33 ] suggested the length and weight content of basalt fiber as 6 mm and 0.3%, respectively. Through the Marshall test, the optimal asphalt content (OAC) is decided in the research.…”
Section: Materials and Test Methodsmentioning
confidence: 99%
“…Fibers can improve the permanent deformation resistance of asphalt mixture, although the impact is minor. Lou et al [ 60 ] studied the effect of different fiber lengths and mix grades on dynamic stability. For blending with 0.3% BF, fiber lengths of 3, 6, 9, 12, 15 mm and mix types of SUP-13, SUP-20, SUP-25 were used.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%